Greener and fairer: A progressive environmental tax reform for Spain - Christoph Böhringer; Xaquin Garcia-Muros; Mikel González-Eguino (University of Oldenburg, Department of Economics, 2019)
Environmental externalities call for the use of environmental taxes to get prices right and thereby reduce environmental pressures. To date, however, the Spanish government makes only limited use of environmental taxes. One major reason for the policy reluctance are concerns on the regressive impacts of environmental taxes. We argue that policy can hedge against these concerns by means of revenue recycling. More specifically, we assess the impacts of a green tax reform where additional revenues are redistributed lump-sum to Spanish households on an equal-per-capita basis. Based on quantitative evidence from coupled microsimulation and computable equilibrium analyses we find that such a green tax reform leads to a substantial reduction in harmful emissions while having a progressive impact.
Keywords: H23; Q4; Q53; Q54; 330; environmental tax reform; household incidence; computable general equilibrium; microsimulation